Particular features of development and realizations of purposeful complex programs in Ukraine - Самков, О.В.; Климчук, В.П. (Proceedings of National Aviation University (archive), 2004)
Features of development and realization of aviation purposeful complex programs in Ukraine are examined. The necessity of metrology securing of aviation programs as well as decision making process in the logistics system during complex programs development and realization. Examples from the modernization programs of aviation are analyzed.